Gut Microbiota in Bipolar Depression and Its Relationship to Brain Function: An Advanced Exploration - Lu, Qiaoqiao; Lai, Jianbo; Lu, Haifeng; Ng, Chee; Huang, Tingting; Zhang, Hua; Ding, Kaijing; Wang, Zheng; Jiang, Jiajun; Hu, Jianbo; Lu, Jing; Lu, Shaojia; et al. (Frontiers in Psychiatry, 2019)
The mechanism of bipolar disorder is unclear. Growing evidence indicates that gut microbiota plays a pivotal role in mental disorders. This study aimed to find out changes in the gut microbiota in bipolar depression (BD) subjects following treatment with quetiapine, and evaluate their correlations with the brain and immune function. Totally 36 subjects with BD and 27 healthy controls (HCs) were recruited. The severity of depression was evaluated with the Montgomery–Asberg Depression Rating Scale (MADRS). At baseline, fecal samples were collected and analyzed by quantitative polymerase chain reaction (qPCR). T lymphocyte subsets were measured to examine immune function. Near-infrared spectroscopy (NIRS) was used to assess brain function. All BD subjects received quetiapine treatment (300 mg/d) for four weeks, following which the fecal microbiota and immune profiles were reexamined. Here, we first put forward the new concept of brain-gut coefficient of balance (B-GCB), which referred to the ratio of [oxygenated hemoglobin]/(Bifidobacteria to Enterobacteriaceae ratio), to analyze the linkage between the gut microbiota and brain function. At baseline, the CD3+ T cell proportion was positively correlated with log10 Enterobacter spp count, while the correlativity between the other bacteria and immune profiles were negative. Log10 B-GCB was positively correlated with CD3+ T cell proportion. In subjects with BD, counts of Faecalibacterium prausnitzii, Bacteroides–Prevotella group, Atopobium Cluster, Enterobacter spp and Clostridium Cluster IV were higher, while the log10 (B/E) were lower than HCs (B/E refers to Bifidobacteria to Enterobacteriaceae ratio, and represents microbial colonization resistance). After treatment, MADRS scores were reduced while the levels of Eubacterium rectale, Bifidobacteria and B/E increased. The composition of the gut microbiota and its relationship to brain function were altered in BD subjects. Quetiapine treatment was effective for depression and influenced the composition of gut microbiota in patients. Clinical trial registration: http://www.chictr.org.cn/index.aspx, identifier: ChiCTR-COC-17011401, URL: http://www.chictr.org.cn/listbycreater.aspx.